Analysis of clinical efficacy of endo-LIF in the treatment of single-segment lumbar degenerative diseases. (January 2020) - Wu, Wenjie; Yang, Sen; Diao, Wenbo; Wang, Donggui; Guo, Yang; Yan, Ming; Luo, Fei
Highlights: Full-endoscopic translaminar lumbar interbody fusion (Endo-TLIF) is an innovative lumbar surgery. Application of a fusion cage in Endo-TLIF for treatment of lumbar degenerative disease is feasible and effective. The operation is characterized by small trauma, little bleeding, low cost and low risk of nerve injury. Abstract: An innovative concept was proposed to treat the lumbar degenerative diseases with full-endoscopic translaminar lumbar interbody fusion (Endo-TLIF) and the efficacy was evaluated. A total of 44 patients from January 2017 to October 2018 were enrolled, including 20 patients undergoing full-endoscopic TLIF and 24 patients undergoing standard open TLIF. The Visual Analogue Scale (VAS) score, Oswestry Dability Index (ODI) and intervertebral fusion were observed in both groups at the last follow-up. The height and width of intervertebral foramen and height of intervertebral space were evaluated via imaging. Mean follow-up time for all patients 13.2 ± 3.2 months. The average operation time was 184.3 ± 70.6 min in experimental group and 191.1 ± 32.4 min in control group. The amount of bleeding was 38.5 ± 19.5 mL and 214.6 ± 61.6 mL. The VAS score was 4.9 ± 1.0 points in experimental group and 4.8 ± 1.0 points in control group before operation, and 0.8 ± 0.6 points and 0.8 ± 0.7 points at the last follow-up. The ODI was 83.5 ± 7.8% and 87.8 ± 5.9% before operation, and 9.9 ± 3.6% and 9.3 ± 3.7% at the last follow-up. The height and width of intervertebral foramen and height of intervertebral space in both groups were significantly improved ( p < 0.05). The fusion rate at the last follow-up were 95% (19 cases) in experimental group and 92% (22 cases) in control group. Full-endoscopic TLIF is feasible in the treatment of single-segment lumbar degenerative diseases, which is characterized by small trauma, quick recovery and low cost. However, the large-sample long-term follow-up is needed to further evaluate its clinical efficacy and safety.